Varying Transvenous Pressure Gradients in Different Entities of Aortic Stenosis - Veulemans, Verena; Maier, Oliver; Klein, Kathrin; Polzin, Amin; Jung, Christian; Westenfeld, Ralf; Blehm, Alexander; Lichtenberg, Artur; Kelm, Malte; Zeus, Tobias (Cardiology and Cardiovascular Medicine, 2019)
Aims: Enhanced left ventricular end-diastolic pressure (LVEDP) has been shown to be associated with worse outcome after acute myocardial infarction, cardiac surgery and in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Nowadays, pulmonary artery wedge pressure (PCWP) has largely replaced direct measurement of LVEDP but several patient series have demonstrated a poor agreement between both methods. Different AS-entities by the meaning of normal-flow high-gradient (NFHG), paradoxical and true low-flow lowgradient ((p)LFLG) AS may be also linked to high left ventricular filling pressures that can be measured by LVEDP and PCWP. Therefore, we analyzed 1) role and agreement of LVEDP and PCWP in patients with highgrade AS and 2) influence of AS-entities on LVEDP/PCWP pressure gradients. Methods and Results: From 2009 to 2018, a total of 788 patients with highgrade AS prior to TAVR, completed hemodynamic status and echocardiographic data were retrospectively enrolled. LVEDP was significantly higher as the PCWP (23.3 ± 8.4 vs. 19.0 ± 8.9; p<0.0001) and over-all LVEDP and PAWP showed medium correlation (r=0.37, 95%-CI=0.30-0.43; p<0.0001*). Surprisingly, patients with NFHG- (6.2 [4.8-7.5] mmHg) and pLFLG-AS (4.2 [3.2-5.1] mmHg) had a significantly higher transvenous pressure gradient than the LFLG-AS cohort (1.4 [-0.1-2.9] mmHg; p<0.0001 between LFLG- and NFHG-AS; p=0.0336 between LFLG- and pLFLG-AS). However, several influencing factors as main drivers for the transvenous pressure gradient were found in NFHG- and pLFLG-AS but not LFLG entity by multivariate analysis. Conclusion: Our data indicate, that the influence on LVEDP/PCWP pressure gradients differ according to several AS-entities and the underlying pathologies with smallest LVEDP/PCWP pressure gradients in LFLG-AS, supposing that the use o